THE EFFECT OF ORGANIZATIONAL CULTURE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT SIIX ELECTRONICS INDONESIA - Egi Ovando Ovando; Triana Ananda Rustam (SEAN Institute, 2022)
The performance of employees of PT SIIX Electronics Indonesia every month during 2021 occurred as much as damage to goods with an average percentage of 2.41% and the damage every month has a fluctuating target and the damage that occurs, employee performance is suspected to be due to organizational culture and also employee work discipline. The purpose of this research is to determine whether organizational culture and discipline have an influence on employee performance either partially or simultaneously at PT SIIX Electronics Indonesia. The type of research used in this study is descriptive research, this observation is in the form of causal symbolic associative observations, the source of data in this study is primary data using questionnaires, the sample used is probability sampling type, totaling 181 respondents. The analytical tool used is multiple linear regression with the help of SPSS 22. The results partially show organizational culture has an effect on employee performance with a value (6.952 > 1.653) and probability value (0.00 < 0.05), work discipline has an effect on employee performance. with a value (4.943 > 1.653) and a probability value (0.00 < 0.05). Simultaneously organizational culture and work discipline have a simultaneous effect on employee performance with a value (132,638 > 3.89) and probability (0.00 > 0.05). Conclusions according to the hypothesis that organizational culture partially has a significant effect on employee performance at PT SIIX Electronics Indonesia so that hypothesis H1 is accepted, work discipline partially has a significant influence on employee performance at PT SIIX Electronics Indonesia so hypothesis H2 is accepted, organizational culture and work discipline simultaneously has a significant influence on the performance of PT SIIX Electronics Indonesia employees so that the hypothesis H3 is accepted.